Neurotropic B vitamins: analgesic and anti-inflammatory effects - Anton A. Beliaev; Olga V. Kotova; Elena S. Akarachkova (LLC "MEDIAFORMAT", 2020)
Patients with musculoskeletal diseases (MSDs) constitute a heavy burden on the society. Therefore, there is a constant search for safe and efficient methods for treatment of such conditions, in which inflammation underlies the pathogenetic process. Chronic back pain is associated with physical inactivity and other lifestyle factors, such as tobacco consumption, poor dietary habits, overweight, poor sleep quality, and uncontrollable stress. For example, obesity is associated with low-grade chronic systemic inflammation, and is, therefore, a significant risk factor for occurrence and chronicity of back pain. The patient's lifestyle may contribute to MSDs, including chronic MSDs associated with inflammation and decreased functional capacity, both independently or in combination with other risk factors. The most common drugs used for treatment of MSDs are the non-steroidal anti-inflammatory drugs (NSAIDs). However, taking into account the possible NSAID-induced adverse events, the physicians are constantly thinking about ways to reduce the risks. В vitamins (B1, B6 and B12) possess analgesic and anti-inflammatory effects, which are discussed in the paper. When used in combination with NSAIDs, particularly in combination of diclofenac with vitamins B1, B6 and B12, the B vitamins possess some other positive effects contributing to restoration of mobility, pain relief and functional recovery in patients with low back pain. Such combination (diclofenac + vitamins B1, B6 and B12) is represented on the Russian market by Neurodiclovit, the successful use of which is discussed in the case report.